Plant cell biology : a practical approach - Hawes, C. R.; Satiat-Jeunemaitre, Béatrice. (Oxford ; New York : Oxford University Press, 2001)
The 'post genomics' era has seen a surge in demand for the techniques of cell biology, to aid in interpreting the function and location of the cell's myriad proteins and macromolecules. This new edition of Plant Cell Biology provides a grounding in established procedures before guiding the reader through the field's most current techniques. It provides advanced undergraduates, postgraduates and research staff in the plant sciences with a uniquelycomprehensive guide to this rapidly expanding discipline.
Introduction to optical microscopy for plant cell biology / P.J. Shaw -- Fluorescent probes for living plant cells / Mark Fricker, [and others] -- Flow cytometry / Teodoro Coba de la Pena, Spencer Brown -- Transient expression, a tool to address questions in plant cell biology / Jane L. Hadlington, Jurgen Denecke -- The green fluorescent protein (GFP) as reporter in plant cells / Jean-Marc Neuhaus, Petra Boevink -- Microinjection / Michael Knoblauch -- Micromanipulation by laser microbeam and optical tweezers / Karl Otto Greulich -- Electrophysiological methods : monitoring exo- and endocytosis in real time / Gerhard Thiel, Jens-Uwe Sutter, Ulrike Homann -- Plant histology / Jackie Spence -- Immunocytochemistry for light microscopy / Beatrice Satiat-Jeunemaitre, Chris Hawes -- Electron microscopy / Chris Hawes, Beatrice Satiat-Jeunemaitre -- In situ hybridization / A.R. Leitch [and others] -- Organelle isolation / David G. Robinson, Giselbert Hinz.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Botanical microscopy -- Technique; Plant cytochemistry -- Technique; Plant cells and tissues; Plantes -- Microscopie -- Technique; Cytochimie végétale -- Technique; Plantes -- Cellules et tissus; SCIENCE -- Life Sciences -- Cell Biology; Botanical microscopy -- Technique; Plant cells and tissues; Plant cytochemistry -- Technique; Planten; Cytochemie; Microscopie